The histological studies in spleen and bursa of fabricius of hormonally thymectomised chickens - Mustafa Sandıkçı (Eurasian Journal of Veterinary Sciences)
In this study, the effect of hormonal thymectomy induced by hydrocortisone acetate (HCA) administration at post hatching period on the spleen and bursa of Fabricius ol chickens was investigated ligth microscopically. For these purpose, 200 chickens from Avian Bred were used as materials. While 100 chickens served as a controls, 100 chickens were hormonally thymectomized by subcutaneous hydrocortisone acetate administration at one week old. At 2, 4, 6 days following the HCA treatment, it was demonstrated that spleens reduced Ihe size, the frequency of lymphocyte decreased and germinal centers disappeared. In these periods, alpha-naphthyl acetate esterase (ANAE) positive lymphocyles lound in peri arteri olar lymphatic sheath in the control group, but the ANAE-positive cells were not observed in the HCA treated group. By the 3rd week following the HCA treatment, ANAE pozitive lymphocytes were rarely seen in the peri arteriolar lymphatic sheath in comparison with control group. After wards, the spleens of HCA-treated animals had quite similar histology with those of the controls. At the 2. 4, 6 days following the HCA treatment, bursa of Fabricii of the animals were displayed advanced atrophy, the cortical region of lymphoid follicles was almosl disappeared, cystic structures were observed in the centres of lymphoid follicles. In these periods, a number of ANAE positive lymphocytes were found in the medullar regions of lymphoid follicles and few ANAE positive lymphocytes found under the follicle associated epithelium (FAE). whereas in the HCA-treated animals the cells did not appear beneath the FAE. Bursa Fabricii of HCA-treatment group displayed quite similar with those of the controls, at subsequent periods of the experiment.